2011
DOI: 10.1002/esp.2125
|View full text |Cite
|
Sign up to set email alerts
|

The influence of alongshore and cross‐shore wave energy flux on large‐ and small‐scale coastal erosion patterns

Abstract: A strong low-pressure system traveled along the Japanese main island Honshu in October 2006. High waves and storm surge attacked the Kashima Coast resulting in huge erosion over the area. Airborne laser data measured in October 2005 and November 2006 were analyzed to estimate cross-sectional changes within the subaerial zone. The results of the alongshore distribution of the changes of cross-sectional area indicate that the amount of erosion of the 38 km-long northern and 15 km-long southern parts decreased to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(27 reference statements)
1
6
0
Order By: Relevance
“…transverse ridges on the inner shelf) that locally focus wave energy and therefore cause alongshore variations in dune erosion. Similar findings have also been reported by Bender & Dean (2003), Schupp et al (2006) and (Galal & Takewaka (2011). Thornton et al (2007) related localized erosional hot-spots to the presence of persistent rip channels.…”
Section: Introductionsupporting
confidence: 88%
“…transverse ridges on the inner shelf) that locally focus wave energy and therefore cause alongshore variations in dune erosion. Similar findings have also been reported by Bender & Dean (2003), Schupp et al (2006) and (Galal & Takewaka (2011). Thornton et al (2007) related localized erosional hot-spots to the presence of persistent rip channels.…”
Section: Introductionsupporting
confidence: 88%
“…The northern end of the beach widened by c. 30 m and the central part of the beach receded by c. 40 m over a relatively brief period (a few months), owing to a higher frequency of southerly storms and/or a lower frequency of easterly storms over this period. The importance of both cross-shore and longshore sediment-transport processes in controlling storm response was further highlighted by Galal and Takewaka (2011), who used LiDAR data to study the response of a 53-km-long section of beach on the Japanese main island Honshu to high waves and storm surge. Using SWAN wave modelling to estimate wave conditions along the coast during an extreme storm, they found that the distribution of energy flux explains the observed erosion pattern quite well: alongshore variability in cross-shore energy flux was responsible for the large-scale variability in erosion, whereas gradients in the alongshore energy fluxes caused shorter-scale variability.…”
Section: Spatial and Temporal Variability And Patternsmentioning
confidence: 99%
“…The large‐scale and long‐term evolution of nearshore sandbars is important for coastal management because sandbars induce depth‐limited wave breaking, while sandbar–shoreline coupling can result in alongshore variability in dune erosion (Thornton et al ., 2007; Galal and Takewaka, 2011; Castelle et al ., 2015). Most existing sandbar (Wright and Short, 1984; Lipmann and Holman, 1990; Van Enckevort and Ruessink, 2003; Splinter et al ., 2011) and sandbar–shoreline coupling (Ruessink et al ., 2007; Castelle et al ., 2010a,b; Price and Ruessink, 2013; Van de Lageweg et al ., 2013) studies were, however, limited to individual shorelines, with spatial scales up to kilometres and timescales up to years.…”
Section: Introductionmentioning
confidence: 99%